Early Removal of the Urinary Catheter After Total or Tumor-Specific Mesorectal Excision for Rectal Cancer Is Safe. Issue 7 (July 2015) - Yoo, Byung Eun; Kye, Bong Hyeon; Kim, Hyung Jin; Kim, Gun; Kim, Jun Gi; Cho, Hyeon-Min
Abstract : BACKGROUND: Total or tumor-specific mesorectal excision can preserve pelvic autonomic nerves during rectal cancer surgery and minimize urinary dysfunction. However, urinary catheterization several days in duration is a common practice after total or tumor-specific mesorectal excision. OBJECTIVE: This study aimed to evaluate the optimal duration of urinary catheterization after total or tumor-specific mesorectal excision for rectal cancer. DESIGN: This is a retrospective review of patients who underwent total or tumor-specific mesorectal excision for rectal cancer. SETTINGS: This study was performed in the colorectal division of a university-affiliated hospital. PATIENTS: Between March 2009 and February 2013, 236 patients fulfilled the inclusion criteria. Patients who underwent combined pelvic surgery and those who had postoperative complications with a Dindo grade III or more and a known urinary disease were excluded; the remaining 189 patients were evaluated. MAIN OUTCOME MEASURES: The primary outcome measure of this study was the incidence of postoperative urinary retention. RESULTS: The incidence of acute urinary retention was 4.8%. Urinary retention was not associated with the postoperative urinary catheterization duration ( p = 0.99). Patients were assigned to 2 groups according to urinary catheterization duration (1 vs ≥2 days). No significant differences were observed between the 2 groups regarding urinary retention (4.8% for 1 day vs 4.7% for ≥2 days; p = 1.0). In a logistic regression analysis, age, sex, ASA classification, surgical procedure, surgical approach, stage, distance from the anal verge, rate of preoperative radiotherapy, duration of urinary catheterization, and time period of surgery were not associated with urinary retention. LIMITATIONS: This was a retrospective, single-center study. There is potential for selection bias. CONCLUSIONS: Our study showed that the urinary catheter could be safely removed on the first postoperative day after total or tumor-specific mesorectal excision.